Difusi Kebijakan Upaya Fundamental Kebijakan Pemerintah Daerah - Lesmana Rian Andhika (Research and Development Agency Ministry of Home Affairs, 2018)
Many local level policy is cancelled policy diffusion can be a tool to improve the quality of policy. The learning process and policy adoption of going through the process selection policies from elsewhere. The purpose of this research more effort into explaining the mechanism of policy diffusion issues, and to generate policies for local governments some from the scientific literature. This research article using a descriptive with argumentation theory method (meta-reasoning or meta-argumentation). Furthermore, this method can be used to provide arguments that claimed to follow from a reason to give support basic truth and reinforce or deny something opinions. The results of these research findings the policy diffusion can guide policymakers with better in order to predict and estimate the policy adequately is beneficial for adoption. Policy diffusion will more easily and successfully implement in places that have adopted from the proximity of the culturally, geographically, interests, and history. On the other hand, policy diffusion is not always concluded with the good caused by various influences such as the capacity and quality human resources of policy makers and implementers, the condition political process between legislative and executive.